Penyuluhan Kesehatan Gigi dan Pelatihan Senam Poco-Poco sebagai Salah Satu Upaya Pencegahan Demensia pada Warga Lansia Seksi Kerasulan Keluarga Paroki Maria Bunda Karmel Jakarta Barat - Wijaya, Harryanto v; Yusra, Yohana; Juslily, Marta; Nauli Komala, Olivia (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Dementia is a neurodegenerative syndrome caused by chronic and progressive disorders accompanied by a decline in brain function that affects emotions, memory, decision-making, behavior, and other brain functions, which disrupt daily activities. The increasing life expectancy in Indonesia may lead to more people experiencing dementia. Recent research reports that poor oral health, such as periodontitis and tooth loss, are linked to dementia. The elderly population tends to have worse dental and oral health compared to other age groups because most of them lack awareness of maintaining dental health due to a lack of education. Dementia is currently medically incurable, making prevention efforts essential. Poco-poco exercises involve movements similar to brain exercises and can help prevent dementia. The pandemic has led to reduced activity levels and fewer visits to dentists among the elderly. The objective is to prevent and slow down dementia, especially Alzheimer's dementia. There were 62 participants in the activity, and the material was presented in the form of PowerPoint and video. The implementation of dental health education and poco-poco exercise training proved to be effective, as there was an increase in the elderly's knowledge, shown by statistically significant differences and an increase in median values between pre-test and post-test results for the participants.